Genetic divergence among threespine stickleback that differ in nuptial coloration. (18th June 2022) - Jenck, Clara S.; Lehto, Whitley R.; Hunnicutt, Kelsie E.; Murphy, Shannon M.; Quinn, Thomas W.; Larson, Erica L.; Tinghitella, Robin M.
Abstract: Sexual signals are shaped by their intended and unintended receivers as well as the signalling environment. This interplay between sexual and natural selection can lead to divergence in signals in heterogeneous environments. Yet, the extent to which gene flow is restricted when signalling phenotypes vary across environments and over what spatial scales remains an outstanding question. In this study, we quantify gene flow between two colour morphs, red and black, of freshwater threespine stickleback fish ( Gasterosteus aculeatus ). We capitalize on the very recent divergence of signalling phenotypes in this system to characterize within‐species and among‐morph genetic variation and to test for levels of gene flow between colour morphs in Oregon and Washington. Despite limited evidence for assortative mating between allopatric red and black populations, we found that black populations are genetically distinct from nearby red populations and that the black morph appears to have evolved independently at least twice in Oregon and Washington. Surprisingly, we uncovered a group of stickleback in one small coastal stream, Connor Creek, which is genetically and morphologically distinct from the red and black colour morphs and from marine stickleback. Historically, both colour morphs have coexisted in this location and sometimes hybridized, raising new questions about the origins and history of these fish, which were first described as anadromous‐black hybrids >50 years ago. Understanding how genetic variation is currently partitioned within and among populations and colour morphs in this system should prompt future studies to assess the relative roles of habitat, ecological and pre‐ and post‐reproductive barriers in the genetic divergence and phenotypic patterns we observe in nature. Abstract : The interplay between natural and sexual selection can lead to divergence in animal signals in heterogeneous environments. But how much is gene flow restricted when signals vary across environments, and over what spatial scales? We characterized within‐species and among‐morph genetic variation and gene flow between two colour morphs of three spine stickleback (red and black). We found that black stickleback populations are genetically distinct from nearby red populations and that the black morph evolved independently at least twice in northwest North America.